2017
DOI: 10.18203/2320-1770.ijrcog20173446
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic aspects of male infertility

Abstract: Background: Infertility affects 10-15% of couples worldwide with rates steadily increasing in the Industrialized world, in part due to the deterioration of male reproductive health.Methods: This study was performed in an attempt to clarify the associated factors that might play a role in group of Indian infertile men. This study was a cross – sectional descriptive study conducted in Karpaga Vinayaga Institute of Medical Sciences. The information was obtained from the men who had attended the clinic from Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…[11] In an Indian epidemiological study on male infertility, the cause of infertility was pure male factor in 31.6% and the problem lay with both male and female partners in 20.4%. [12] Recent study shows that the prevalence of obesity in India ranges from 13% to 50% of urban and 8-38.2% of the rural population. [13] The paradigm shift to obesity can be attributed to sedentary lifestyle and consumption of energydense food.…”
Section: Discussionmentioning
confidence: 99%
“…[11] In an Indian epidemiological study on male infertility, the cause of infertility was pure male factor in 31.6% and the problem lay with both male and female partners in 20.4%. [12] Recent study shows that the prevalence of obesity in India ranges from 13% to 50% of urban and 8-38.2% of the rural population. [13] The paradigm shift to obesity can be attributed to sedentary lifestyle and consumption of energydense food.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, approximately 15% of reproductive aged couples have the problem of infertility. 1 , 2 Male infertility has been found to be a major contributing factor to the overall infertility cases in Saudi Arabia. 3 , 4 A one year retrospective study conducted on infertile couples reported a prevalence of approximately 19% male infertility cases in the eastern province region of Saudi Arabia.…”
mentioning
confidence: 99%
“…Concerning male infertility, Agarwal et al, in a systematic review, found higher rates of male infertility in Central and Eastern Europe (8-12%), Australia (8-9%) and Europe (7.5%) than North America (4.5-6%) and Sub-Saharan Africa (2.5-4.8%) [7]. Recent studies in India found a frequency of 20.4% of pure male factor in infertile couple, associated with several factors such as a history of varicocele surgery, STI, alcohol consumption, diabetes, small size testis and tobacco [8,9]. One-third of these patients had erectile dysfunction while half had azoospermia or oligospermia [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in India found a frequency of 20.4% of pure male factor in infertile couple, associated with several factors such as a history of varicocele surgery, STI, alcohol consumption, diabetes, small size testis and tobacco [8,9]. One-third of these patients had erectile dysfunction while half had azoospermia or oligospermia [8]. In China, Cong et al found an increased risk of infertility in those engaged in occupations with the high-temperature working environment [10]; while tobacco (29%) and history of varicocele surgery (22%) were the main risk factors for male infertility in Iran [11].…”
Section: Introductionmentioning
confidence: 99%